2009
DOI: 10.1097/scs.0b013e318192801b
|View full text |Cite
|
Sign up to set email alerts
|

Palatoplasty Outcomes in Nonsyndromic Patients With Cleft Palate

Abstract: The primary objective of cleft palate repair is velopharyngeal competence without fistula. The reported incidence of fistula and velopharyngeal insufficiency (VPI) is variable. Our purpose was to assess the senior surgeon's 29-year palatoplasty experience with respect to incidence of fistula and VPI. Our hypotheses were that VPI is related to (1) age at palatoplasty, (2) cleft palate type, and (3) VPI and palatal fistula incidence decrease with the surgeon's experience. We reviewed the records of all children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
131
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 29 publications
7
131
3
Order By: Relevance
“…Although the presence of velopharyngeal insufficiency requiring secondary surgery has been shown to follow the Veau hierarchy, 1,[8][9][10][11] other reports have found the highest incidences in isolated cleft palate (Veau I and II). [12][13][14][15][16][17] Conversely, Marrinan et al could find no correlation between velopharyngeal insufficiency and Veau hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of velopharyngeal insufficiency requiring secondary surgery has been shown to follow the Veau hierarchy, 1,[8][9][10][11] other reports have found the highest incidences in isolated cleft palate (Veau I and II). [12][13][14][15][16][17] Conversely, Marrinan et al could find no correlation between velopharyngeal insufficiency and Veau hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…The American Cleft Palate-Craniofacial Association advocates repair by 18 months in a normally developing infant [8]. Certain centers support earlier repair to reduce the risk of velopharyngeal insufficiency, which has been shown to increase by 6% for each month the repair is delayed beyond 7 months [9,10].…”
mentioning
confidence: 99%
“…Repositioning of the levator sling and recreation of the normal anatomy results in velopharyngeal competence for most patients and reduces the need for secondary pharyngeal flaps. 27 In a study by Sullivan et al, 28 persistent postoperative velopharyngeal insufficiency was shown to be associated with patient age at palatoplasty (timing), and degree of palatal involvement (Veau score) (Level of Evidence: Therapeutic/ Prognostic, IV). They conclude that early, singlestage repair reduces the development of learned, compensatory misarticulations that can persist despite surgical correction of the palatal anatomy, but must be weighted against altered facial growth secondary to early disruption of the maxillary periosteum and soft-tissue envelope.…”
Section: Speech Outcomesmentioning
confidence: 98%